ENGINEERING THE NANOPORE EDGE OF GRAPHENE USING FUNCTIONAL GROUPS AND DOPING TO ENHANCE SODIUM ADSORPTION AS THE CANDIDATE FOR AN ANODE SODIUM-ION BATTERY - Nenni
Using renewable energy sources is one effort to reduce the greenhouse effect caused by fossil fuels. Because renewable energy sources are intermittent, the energy storage technology that can be used anytime and anywhere is required. The sodium-ion battery (SIB) as an alternative energy storage system to the lithium-ion battery (LIB) shows tremendous potential. Still, it has issues, such as low capacity and rate due to its sizeable ionic size (Na), which complicates the intercalation process into the graphite structure (commonly used in LIB). One of the reasons Na cannot form graphite intercalation compounds is the local interaction repulsion between Na and a single layer of graphene. Inadequate interaction contributes to a reduction in Na storage capacity. The formation of a nanopore as a Na-binding site in the structure of graphene has succeeded in increasing the adsorption ability of Na. Because the nanopore formation usually results in different graphite edges with varying reactivity (which have the potential to increase Na adsorption), the nanopore motif must be reviewed to obtain the most optimal configuration for Na binding.